2019
DOI: 10.1177/0194599819874315
|View full text |Cite
|
Sign up to set email alerts
|

Margins in Laryngeal Squamous Cell Carcinoma Treated with Transoral Laser Microsurgery: A National Database Study

Abstract: Objectives To determine national positive margin rates in transoral laser microsurgery, to compare patients with positive and negative margins, and to identify factors associated with positive margins. Study Design Retrospective review of the National Cancer Database. Setting Population based. Subjects/Methods Patients included those with TIS-T3 laryngeal squamous cell carcinoma (2004-2014). Univariable and multivariable logistic regression were used to identify predictors. Results A total of 1959 patients met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…The National Cancer Database study from the USA assessed positive margin rates in trans-oral laser microsurgery of LSCC. Cases treated at non-academic centers and those with lower caseloads had a higher likelihood of positive margins [ 21 ]. Silverman et al showed that postoperative radiotherapy of T1-T2 LSCC was significantly more common in low-volume centers [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The National Cancer Database study from the USA assessed positive margin rates in trans-oral laser microsurgery of LSCC. Cases treated at non-academic centers and those with lower caseloads had a higher likelihood of positive margins [ 21 ]. Silverman et al showed that postoperative radiotherapy of T1-T2 LSCC was significantly more common in low-volume centers [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, intensive individual counseling is fundamental. Two prerequisites for safe endoscopic resection are optimal anatomical exposure of the tumor and sufficient expertise and caseload of the institution and the individual surgeon [ 81 ]. There should be no doubt that R0 resection is safely achievable.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is consistent with the finding in our observational cohort study: the adjusted HR was 3.5 (95%-CI: 2.2–5.7) for advanced N stage [ 30 ]. In many other studies, N stage, especially advanced N stage N2–3, was reported as an independent negative prognostic marker [ 26 , 27 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For surgery, laser surgery is an option only in selected cases of T3 laryngeal cancer [ 55 , 56 ]. If it is chosen, the result is largely dependent on the expertise of the surgeon and the caseload of the facility [ 31 ]. The most effective and comparable surgery for the comparison of efficacy between surgical and nonsurgical treatment in T3 laryngeal cancers is total laryngectomy (TL).…”
Section: Discussionmentioning
confidence: 99%